Potential Development Of TMDL By Using Water Quality Modelling in Malaysia: A Review - Siti Aishah, Che Osmi; Wan Faizal, Wan Ishak; Siti Fatimah, Che Osmi; Mohammad Adam, Azman (2016)
The issues of water quality and water pollution have been a major problem across the country. A lot of management attempt to develop the TMDL database in order to control the river pollution. Over the past decade, the mathematical modeling has been used as a tool for the development of TMDL. In Malaysia, the determination of water quality status are evaluate by using Water Quality Index (WQI) for river water quality. This paper present the potential to develop the total maximum daily load (TMDL) implementation by using water quality modelling in Malaysia. To obtain the reliable database of TMDL, the appropriate water quality modeling should be choose as a based on the available data provided. This paper will discuss the use of several water quality modeling such as QUAL2E, QUAL2K, and EFDC to develop TMDL. The attempts to integrate several modeling are also been discuss in this paper. According to this paper, the differences in the application of water quality modeling based on their properties shows their ability to develop the modeling for TMDL, as well as good examples to be applied in Malaysia.